Injury volume extracted from MRI predicts neurologic outcome in acute spinal cord injury: A prospective TRACK-SCI pilot study. (December 2020) - Mummaneni, Nikhil; Burke, John F.; DiGiorgio, Anthony M.; Thomas, Leigh H.; Duong-Fernandez, Xuan; Harris, Mark; Pascual, Lisa U.; Ferguson, Adam R.; Russell Huie, J.; Pan, Jonathan Z.; Hemmerle, Debra D.; Singh, Vineeta; et al.
Highlights: The volume of MRI lesions after SCI predicts injury severity. The degree of correlation of injury severity with MRI volume is greater than two-dimensional metrics of MRI lesions. These data suggest that there a high degree of diagnostic information in the volume of an MRI lesion after SCI. Abstract: Conventional MRI measures of traumatic spinal cord injury severity largely rely on 2-dimensional injury characteristics such as intramedullary lesion length and cord compression. Recent advances in spinal cord (SC) analysis have led to the development of a robust anatomic atlas incorporated into an open-source platform called the Spinal Cord Toolbox (SCT) that allows for quantitative volumetric injury analysis. In the current study, we evaluate the prognostic value of volumetric measures of spinal cord injury on MRI following registration of T2-weighted (T2w) images and segmented lesions from acute SCI patients with a standardized atlas. This IRB-approved prospective cohort study involved the image analysis of 60 blunt cervical SCI patients enrolled in the TRACK-SCI clinical research protocol. Axial T2w MRI data obtained within 24 h of injury were processed using the SCT. Briefly, SC MRIs were automatically segmented using the sct_deepseg_sc tool in the SCT and segmentations were manually corrected by a neuro-radiologist. Lesion volume data were used as predictor variables for correlation with lower extremity motor scores at discharge. Volumetric MRI measures of T2w signal abnormality comprising the SCI lesion accurately predict lower extremity motor scores at time of patient discharge. Similarly, MRI measures of injury volume significantly correlated with motor scores to a greater degree than conventional 2-D metrics of lesion size. The volume of total injury and of injured spinal cord motor regions on T2w MRI is significantly and independently associated with neurologic outcome at discharge after injury.